Pilot study on the application of the NQLS questionnaire in a study of physical activity in inhabitants of villages and towns [Pilotní studie využití dotazníku NQLS v kontextu s pohybovým chováním obyvatel vesnice a města] - Dagmar Sigmundová; Erik Sigmund; Karel Frömel; Petra Vlková (Palacky University, 2009)
BACKGROUND: The environment of a neighborhood (the availability of sports facilities, services, and transportation) can influence physical activity (PA), however the influence of different environments on PA have not been clearly described in the Czech Republic yet. OBJECTIVE: The aim of the study is to identify the relationships between obesity and PA in Olomouc and the surrounding countryside depending on differences in the neighborhood environment. A further aim of the study is to form recommendations concerning physical activity enhancement and lifestyle. METHODS: PA was quantified on the basis of the NQLS (Neighborhood Quality of Life Study) questionnaire, which includes the internationally standardized IPAQ long questionnaire in its second part. The study involved 241 valid questionnaires from the respondents from Olomouc (capital of Olomouc region, 100,000 inhabitants) and Praksice (village close to Olomouc, less than 1,000 inhabitants) aged 15-60 (102 men and 139 women). The data adjustment was done in compliance with the international guidelines of the "IPAQ Research Committee" (www.ipaq.ki.se). RESULTS: Based on individual values, 6% of the inhabitants of Olomouc and 2% of inhabitants of Prakšice show very low physical activity, 23% of the inhabitants of Olomouc and 11% of inhabitants of Praksice meet minimal PA requirements, and 66% of the inhabitants of Olomouc and 87% of inhabitants of Praksice show higher levels of physical activity. Both the inhabitants of the town and the village confirm the good availability of services such as grocery stores, elementary schools and post offices. In both the town and the village, the inhabitants also claim that there is good availability of pedestrian and cycling paths. The inhabitants of the village show higher physical activity than the inhabitants of the town. CONCLUSIONS: The young and middle aged inhabitants of the village show significantly higher PA than the inhabitants of the town. The majority of the inhabitants of both Olomouc and Praksice are physically active enough. In overweight or obese women, we recommend including vigorous PA which does not overstress the muscular skeletal system or to increase the overall PA to the required level by increasing the volume of walking and moderate PA. We also advocate for a change of the entire lifestyle. [VÝCHODISKA: Odlišné prostředí místa bydliště (dostupnost sportovišť, služeb, dobrá dopravní obslužnost...) může ovlivňovat pohybovou aktivitu (PA), avšak tento vliv ani rozdíly v prostředí nebyly v České republice dosud detailně zdokumentovány. CÍLE: Cílem této studie je poukázat na vztah obezity a PA v Olomouci a na venkově v závislosti na odlišném prostředí místa bydliště. Dílčím cílem je snaha o formulaci doporučení podporující pohybově aktivní životní styl. METODIKA: PA byla kvantifikována na základě dotazníku NQLS (Neighborhood Quality of Life Study), který ve své druhé části obsahuje mezinárodně standardizovaný dotazník IPAQ long, dlouhou administrativní verzi. Do studie bylo zahrnuto 241 validních dotazníků od respondentů z Olomouce a Prakšic ve věku 15-60 let (102 mužů a 139 žen). Úpravy získaných dat byly provedeny v souladu s mezinárodně stanovenou metodikou vyhodnocování "IPAQ Research Committee" (www.ipaq.ki.se). VÝSLEDKY: Dle individuálních hodnot je 6 % obyvatel Olomouce a 2 % obyvatel Prakšic velmi málo aktivních, 23 % obyvatel v Olomouci a 11 % obyvatel v Prakšicích splňuje minimální požadavky na PA a 66 % v Olomouci a 87 % v Prakšicích vykazuje vyšší úroveň pohybové aktivity. Obyvatelé města i vesnice uvádějí dobrou dostupnost služeb typu malý obchod s potravinami, základní škola a pošta. Stejně pozitivně je ve městě i na vesnici hodnoceno chodecké prostředí se stezkami pro chodce a pro cyklisty. Obyvatelé vesnice vykazují vyšší pohybovou aktivitu, než obyvatelé města. ZÁVĚRY: Obyvatelé vesnice mladšího a středního věku vykazovali signifikantně více PA než obyvatelé města. Většina obyvatel Olomouce i Prakšic je dostatečně pohybově aktivních. U žen s nadváhou a obezitou doporučujeme vyšší zařazení absentující PA intenzivnějšího charakteru, které nadměrně nezatěžuje pohybový aparát, nebo zvýšit celkovou PA na přijatelnou úroveň vyšším objemem chůze a PA střední intenzity. Pozornost by měla být zaměřena na celkovou změnu životního stylu.]